1999
DOI: 10.1006/viro.1999.9979
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p53 Tumor Suppressor by Hepatitis C Virus Core Protein

Abstract: In addition to being a structural protein that packages the viral genomic RNA, hepatitis C virus (HCV) core protein possesses regulatory functions. In this report, we demonstrate that the HCV core protein could enhance the gene transactivation activity of the tumor suppressor p53, regardless of whether p53 was derived from an exogenous or an endogenous gene. The activation of p53 by the HCV core protein was supported by the observation that the HCV core protein could enhance the expression of p21(waf1/Cip1), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
86
6
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(95 citation statements)
references
References 29 publications
2
86
6
1
Order By: Relevance
“…In this work, we presented evidence showing that HCV core protein and p53 associate both in vitro and in vivo, and colocalize at the perinuclear region and the subnuclear granular structures. Moreover, different from the findings by Lu et al (1999) and Otsuka et al (2000) that p53 transactivational activity is enhanced by HCV core protein, our results show that while low level of HCV core protein cooperates with p53 to transactivate the p53-responsive promoter activity, higher level of HCV core protein on the other hand downregulates the p53-mediated transactivation. Surprisingly, regardless of the activation or suppression of p53-dependent transcription, HCV core protein enhances the in vitro p53 DNA-binding affinity, presumably attributed by the induction of hyperacetylation of p53 at Lys 373 and Lys 382 residues.…”
Section: Introductioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In this work, we presented evidence showing that HCV core protein and p53 associate both in vitro and in vivo, and colocalize at the perinuclear region and the subnuclear granular structures. Moreover, different from the findings by Lu et al (1999) and Otsuka et al (2000) that p53 transactivational activity is enhanced by HCV core protein, our results show that while low level of HCV core protein cooperates with p53 to transactivate the p53-responsive promoter activity, higher level of HCV core protein on the other hand downregulates the p53-mediated transactivation. Surprisingly, regardless of the activation or suppression of p53-dependent transcription, HCV core protein enhances the in vitro p53 DNA-binding affinity, presumably attributed by the induction of hyperacetylation of p53 at Lys 373 and Lys 382 residues.…”
Section: Introductioncontrasting
confidence: 99%
“…In comparison to the findings by Lu et al (1999) and Otsuka et al (2000), our reporter analyses indicate that HCV core protein has dual effects on p53-mediated transactivation depending on viral protein concentration: inhibition at high level of expression and coactivation by low level of HCV core protein (Figure 4). We also showed that the acetylation and phosphorylation states of p53 are significantly altered in cells expressing HCV core protein (Figure 6).…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Because p53 maintains the genetic integrity of cells by controlling progression through the cell cycle, the loss of p53 function, therefore, appears to be associated with increased genetic instability and the accumulation of mutations, which is likely to precede oncogenic transformation (Levine, 1993). Various tumor viruses encode proteins that interact with p53, including T antigen from SV40 (Lane and Crawford, 1979), E6 from human papillomavirus (Dyson et al, 1989), E1B 55-kDa from adenovirus (Sarnow et al, 1982), HBx from HBV (Wang et al, 1994(Wang et al, , 1995Ueda et al, 1995), and core protein from HCV (Otsuka et al, 2000;Ray et al, 1997;Lu et al, 1999). Most of the p53-interacting viral proteins were reported to suppress p53 function (Scheffner et al, 1992;Wang et al, 1994Wang et al, , 1995Dobner et al, 1996;Muralidhar et al, 1996;Uchida et al, 1996;Elmore et al, 1997;Mulloy et al, 1998;Pise-Masison et al, 1998;Prost et al, 1998;Ray et al, 1997;Sheppard et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Recent studies have highlighted the importance of this gene in the oncogenesis of hepatocellular carcinoma, cholangiocarcinoma and ovarian adenocarcinoma. [9][10][11] Overexpression of the p53 gene in keratinocytes above and adjacent to the cornoid lamella in porokeratosis lesions has also been demonstrated, resulting in early apoptosis and abnormal differentiation of these cells. This finding suggests its involvement in the pathogenesis of these lesions.…”
Section: Discussionmentioning
confidence: 99%